Le vol, l’ordinateur et le contrôle comptable - Bismuth, Claude C.; Giard, Yves (Assurances, 1981)
Electronic processing has opened the door to many frauds unheard of until today. Chartered accountants have thus had to work closely with clients in an attempt to prevent and to detect quickly computer frauds. In their article, Messrs. Bismuth and Giard point out the need for management to exercise over the operations and access to their systems, and for the auditors to conduct a periodic review of the computer systems as part of their annual audit. Computer security reviews can be the subject of a special assignment whereby the auditor can use his knowledge.